Foundation of Voronezh State University - M. D. Karpachev (Moscow Polytechnic University, 2018)
The article is devoted to the history of foundation of University in Voronezh. The idea of establishing a regional university appeared since the beginning of  the 19th century. This issue had already been discussed by Voronezh  society and the educational community. Nevertheless, the implementation of  this idea became possible only in 1918 when the Russian teaching staff of  former Yuriev (Derpt) University was evacuated from Estonia to Russia. This  relocation was not a random event since Voronezh was an administrative,  economic and cultural centre of Black Earth Region of Russia. In the early  XIX it had been planned that it would be one of the Russian cities where the  universities should be open. In 1879 the newspaper Novoe vremya published the article "Voronezh University" where the author raised the  question of establishing a University. In 1907-1908 the idea was  substantiated by an eminent geographer P. Semenov- Tyan-Shansky. And  only in spring 1918, when Yuriev was occupied by Germans and the  professors of Yuriev University were looking for a new location, the question  was settled at the governmental level. In autumn 1918 the first lecture was  delivered and the history of Voronezh University began.